The Data-Acquisition System with Cluster-Finding Trigger at the J-PARC KOTO Experiment. (April 2020) - Lin, C; Hsiung, Y B; Wah, Y W; Tung, Y C; Luo, Y T; Bogdan, M
Abstract: In order to collect the events efficiently with a high intensity beam, we built a new trigger electronics system based on the calibrated energy information and the number of electromagnetic shower clusters in the calorimeter for the J-PARC KOTO experiment. The dead time of this system is 0.16 µs and the loss was measured to be less than 1%. By performing the online clustering algorithm on the simulated data, the trigger efficiency for the primary mode K L → π 0 ν ν ¯ is estimated to be 99.6%.